Evaluation of the technical performance of three different commercial digital breast tomosynthesis systems in the clinical environment. Issue 6 (June 2016) - Rodríguez-Ruiz, A.; Castillo, M.; Garayoa, J.; Chevalier, M.
Highlights: We describe the technical performance characteristics of three DBT systems. The influence of DBT acquisition parameters on image quality is researched. We compare the detector and AEC performance respect to 2D mammography. In-plane and in-depth resolutions as well as artefact spreading of DBT were analysed. Mean glandular dose was assessed for PMMA phantoms with different thickness. Abstract: The aim of this work was to research and evaluate the performance of three different digital breast tomosynthesis (DBT) systems in the clinical environment (Siemens Mammomat Inspiration, Hologic Selenia Dimensions, and Fujifilm Amulet Innovality). The characterization included the study of the detector, the automatic exposure control, and the resolution of DBT projections and reconstructed planes. The modulation transfer function (MTF) of the DBT projections was measured with a 1 mm thick steel edge, showing a strong anisotropy (30–40% lower MTF0.5 frequencies in the tube travel direction). The in-plane MTF0.5, measured with a 25 μm tungsten wire, ranges from 1.3 to 1.8 lp/mm in the tube-travel direction and between 2.4 and 3.7 lp/mm in the chest wall–nipple. In the latter direction, the MTF peak shift is more emphasized for large angular range systems (2.0 versus 1.0 lp/mm). In-depth resolution of the planes, via the full width at half maximum (FWHM) from the point spread function of a 25 μm tungsten wire, is not only influenced by angular range and yields 1.3–4.6 mm among systems. The artifact spread function from 1 mm diameter tungsten beads depends mainly on angular range, yielding two tendencies whether large (FWHM is 4.5 mm) or small (FWHM is 10 mm) angular range is used. DBT delivers per scan a mean glandular dose between 1.4 and 2.7 mGy for a 45 mm thick polymethyl methacrylate (PMMA) block. In conclusion, we have identified and analysed specific metrics that can be used for quality assurance of DBT systems.